(untitled) (PERcursos Linguísticos, 2024)
ABSTRACT: The history of the education of the deaf is a wide field with a succession of themes that require investigation. Among the subjects that deserve highlighting are the pedagogical practices of the Ângela de Brienza School, an institution dedicated to the education of the deaf located in Vitória, state of Espírito Santo, Brazil. That school was founded around the year of 1958 and had its activities shut down in 1971. The goal of this study is to understand the implications generated by the pedagogical practices proposed in the Milan Congress (1880) and their regularities in the Paris Congress (1900 – section of the hearers) in the education of the deaf of Espírito Santo in the mid-20th century. Under the perspective of authors of the field of Foucauldian Studies, we resorted to the concepts of practice in order to analyze the photographs and cutouts of newspapers that mention the Ângela de Brienza School during its existence years. Based on the analysis of these documents it is possible to understand how the regularity of the discursive and non-discursive practices of both European congresses, which happened in the late 19th century, continued circulating among European and American countries, generating effects in the education of the deaf of Espírito Santo during the 20th century. KEYWORDS: History of the education of the deaf. Pedagogical practices. Regularities. Photographs.